Drug utilization study and prescribing patterns in psychiatry patients at a tertiary care hospital - M., Venkatesh Perumal; Bouddh, Surendra Kumar; S. R., Nirmal; Deshpande, Ashok; Singh, Jai; M., Natesh Prabhu (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The Drug utilization research (DUR) compares drug use between different countries and regions and is used to assess the rationality of prescribing pattern of the drug therapy. With this background we decided to evaluate antipsychotic drugs prescribing pattern in the psychiatric patients in a tertiary care hospital. Methods: The study was carried out at Department of Psychiatry, DSMCH. It was open label, cross - sectional, prescribed Documents based study. Duration of the study was one month (May-2017). Out-Patient number, age, sex, diagnosis, prescribed generic name, brand name, dose, route of administration, duration of therapy obtained from the Prescription register of Out - Patient Department of the Psychiatry. Results: The clinical experiences of the Psychiatrist I, II and III were 17 years, 35 years and 10 years respectively. The Psychiatrist I, II and III prescribed treatment for 36 (31.9%), 61 (54%) and 16 (14.2%) patients respectively. Among overall (n=113) patients (average age 38.9 years), male n=56 (49.6%) and female=57 (50.4%) were treated by all the three psychiatrists. The percentage of prescription of various drugs used were: Escitalopram (15.7%), Clonazepam (14.6%), Sertraline (8.7%), Risperidone (7.5%), Propranolol (6.7%), Olanzapine (6.3%), Quetiapine (5.9%), Trihexyphenidyl (5.5%), Amitriptyline (5.1%) and Other prescribed drugs, were between (0.4 to 2.8%). Conclusions: From this study, it can conclude that rational usage of drugs were followed in this study. All three prescribers (Psychiatrist I, II, and III) prescriptions were found to be rationale.